2018
DOI: 10.1007/s00464-018-6398-3
|View full text |Cite
|
Sign up to set email alerts
|

Complications after discharge predict readmission after colorectal surgery

Abstract: Statistical models that include complications identified after discharge predict re-admission. Strategies to reduce re-admission after colorectal surgery should emphasize prevention of complications and more effective interventions to manage and ameliorate evolving complications identified after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that establishment of an ERP may lead to a decrease 8 or no change [9][10][11] in readmissions, that complications are drivers of readmissions, and that patient frailty and disease progression may also contribute. 21,22 However, readmissions are difficult to predict, and the reasons for readmission are complex and may vary from institution to institution. Readmission risk prediction studies are not yet conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that establishment of an ERP may lead to a decrease 8 or no change [9][10][11] in readmissions, that complications are drivers of readmissions, and that patient frailty and disease progression may also contribute. 21,22 However, readmissions are difficult to predict, and the reasons for readmission are complex and may vary from institution to institution. Readmission risk prediction studies are not yet conclusive.…”
Section: Discussionmentioning
confidence: 99%